Application of Various Organic Materials and Urea on Soybean Growth and Production in Nickel Contaminated Soil - S. Sulkifli; Andi Cakra Yusuf (Universitas Sembilanbelas November Kolaka, 2022)
The research was conducted at the Experimental Garden of Hasanuddin University (UNHAS) located in Baraya, Makassar, South Sulawesi from March to June 2022. This research was in the form of experiments conducted in soybean plant pots. The media used was soil obtained from post-nickel mining in Sorowako, East Luwu Regency, South Sulawesi. Research in the field is arranged according to a Randomized Block Design (RAK) with 3 replications. The treatment design used a 2-factor factorial design. The first factor is the type of Organic Material or Compost (K) consisting of 4 levels, namely; K0 (without organic matter), K1 (Kirinyuh compost), K2 (gamal compost) and K3 (rice husk compost) and the second factor is Urea (U) fertilization treatment consisting of 4 levels, namely; U0 (without Urea fertilizer), U1 (100 kg ha–1 Urea), U2 (200 kg ha–1 Urea), U3 (300 kg ha–1 Urea). The number of pots used was 4 units per treatment so there were 192 units of observation. The two factors tested resulted in 16 treatment combinations. The results showed that gamal compost (Gliricidia sepium) gave the best effect in increasing plant height, number of soybean leaves and weight of 100 soybean seeds. The results showed that urea dose of 100 kg ha–1 gave the best effect in increasing plant height and number of soybean leaves. The results showed that there was no interaction between the administration of the type of organic matter and the dose of urea